PERENCANAAN PARTISIPATIF DALAM PEMBERDAYAAN MASYARAKAT - Maryam, Dewi (BINA' AL-UMMAH, 2015)
Village Development PlanningDeliberation (Musrenbangdes) is an annual meeting of village’s stakeholders to discuss Rural Development Work Plan (RKP Desa) and Village Mid-Term Development Work Plan (RPJM Desa).This study examines community participation in Musrenbangdesand development programs implementation in 2014 in Kebumen village, Sumberejo, Tanggamus. This study using qualitative approach relies on document review, in-depth interview, and observation as data collection methods. Data collected is then analyses by using interactive model suggested by Miles and Huberman.This study shows that the level of community participation Murenbangdes is characerised by the following (1) Public participation by attending the meeting reaches 73%; (2) Public participation by contributing ideas is low; (3) Public participation is categorised as placation, that is, the authority allows citizens to provide inputs, but retains decision-making process in their hand. This study also suggests that community participation in development programs implementation is chaacterised by following: (1) development program has not been implemented effectively and participatively; (2) participation in development programs implementation is categorised as therapy, i.e. level of participation is engineered by some parties to replace pure participation.